2019
DOI: 10.1177/1471301219894141
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the perceptions of people with dementia about the social robot PARO in a hospital setting

Abstract: New technology, such as social robots, opens up new opportunities in hospital settings. PARO, a robotic pet seal, was designed to provide emotional and social support for older people with dementia. We applied video-ethnographic methods, including conversational interviews and observations with video recording among 10 patient participants while they were using the robot. We also conducted semi-structured individual interviews and focus groups with nursing staff to gain contextual information. Patient and fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 44 publications
(51 reference statements)
1
44
0
1
Order By: Relevance
“…In expanding the view of dementia beyond a narrow medical approach, technology may be used to empower people with dementia, supporting them to live a more meaningful life. For instance, a recent study suggested that the use of a social robot for hospital patients with dementia promoted a sense of self and facilitated social connection with others (Hung et al, 2019). Arthur (2009) defines technologies as assemblies of practices and components put to use in order to fulfill a specific purpose.…”
mentioning
confidence: 99%
“…In expanding the view of dementia beyond a narrow medical approach, technology may be used to empower people with dementia, supporting them to live a more meaningful life. For instance, a recent study suggested that the use of a social robot for hospital patients with dementia promoted a sense of self and facilitated social connection with others (Hung et al, 2019). Arthur (2009) defines technologies as assemblies of practices and components put to use in order to fulfill a specific purpose.…”
mentioning
confidence: 99%
“…Hung, Lillian; Gregorio, Mario; Mann, Jim; Wallsworth, Christine; Horne, Neil; Berndt, Annette; Liu, Cindy ( 2019) [68] To analyze perceptions of experiences with PARO robots in a hospital setting.…”
Section: Elderlymentioning
confidence: 99%
“…Emotions are connected to social interactions [55]; this is the case for the elderly and (4) dementia patients [53,56]. It is a promising field for the PARO robot [68] and exhibits both benefits and barriers [71]. PARO can support the psychosocial needs of the elderly related to inclusion, identity, attachment, occupation, and comfort [68].…”
Section: (A) Elderlymentioning
confidence: 99%
“…Thereby, the concerns of formal and informal caregivers of persons with dementia should also be considered. The needs of people with dementia might refer to the social robot’s intended use, appearance, functions, and way of delivery [ 24 ]. Considering these needs is indispensable to ensure that social robot interventions have a positive impact on persons with dementia and seem meaningful to them [ 5, 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This also refers to their representatives.Furthermore, there is a lack of information concerning authors' discussions of ethical issues. Thus, our ethical analysis cannot provide specific implications for an ethically responsible intervention development and implementation as it is often demanded[19][20][21][22].Authors of future studies should transparently and clearly describe their theoretical assumptions when reporting social robot interventions as well as potential ethical conflicts and consent procedures [72]. Researchers should provide information on their dementia-related experience in research and practice.…”
mentioning
confidence: 99%